2015
DOI: 10.1371/journal.pone.0129590
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase mRNA Overexpression and Decreased Extracellular Matrix Components Are Early Events in the Pathogenesis of Emphysema

Abstract: To describe the progression of parenchymal remodeling and metalloproteinases gene expression in earlier stages of emphysema, mice received porcine pancreatic elastase (PPE) instillation and Control groups received saline solution. After PPE instillation (1, 3, 6 hours, 3 and 21 days) we measured the mean linear intercept, the volume proportion of types I and III collagen, elastin, fibrillin and the MMP-1, -8, -12 and -13 gene expression. We observed an initial decrease in type I (at the 3rd day) and type III c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 47 publications
0
11
1
5
Order By: Relevance
“…Emphysema is characterized by changes in the organization and composition of extracellular matrix (Ito et al, 2005 ; Suki et al, 2012 ; Szabari et al, 2012 ; Takahashi et al, 2014 ; Robertoni et al, 2015 ). In an attempt to repair the damaged lung, new collagen fibers are resynthesized, but are relatively weak, and, because they can rupture, tend to reduce overall tissue stiffness and static lung elastance (Suki et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Emphysema is characterized by changes in the organization and composition of extracellular matrix (Ito et al, 2005 ; Suki et al, 2012 ; Szabari et al, 2012 ; Takahashi et al, 2014 ; Robertoni et al, 2015 ). In an attempt to repair the damaged lung, new collagen fibers are resynthesized, but are relatively weak, and, because they can rupture, tend to reduce overall tissue stiffness and static lung elastance (Suki et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…ECM components undergo synthesis (104,105) concurrent with ECM breakdown, and each process is influenced by various factors such as increased mechanical stress (106) and tissue aging (107). Thus, it is challenging to identify matrikines that can exert a specific phenotype in diseases where the ECM undergoes continuous remodeling, as is seen in interstitial lung diseases including idiopathic pulmonary fibrosis, ARDS, and COPD.…”
Section: Hyaluronan-derived Matrikinesmentioning
confidence: 99%
“…A wide variety of studies have highlighted the proteolytic activity of elastase in causing structural changes, such as higher mean linear intercept and alveolar enlargement both in mice [71][72][73][74][75] and in rats [76][77][78][79] (Table 2). Furthermore, several studies reported changes in ECM composition after elastase administration, such as disorganized elastin [80,81], degradation of proteoglycans [82], and abnormal collagen remodeling [83][84][85][86][87][88]. However, as in CS models, these effects are dependent on several factors, including strain; enzyme dose at each instillation; and number of elastase challenges (Figure 2).…”
Section: Elastase Instillationmentioning
confidence: 99%